High Temperature and Ethinylestradiol May Reduce Body Growth, Liver and Hepatocyte Volumes and Lipid Droplets in Adult Male Guppies - Margarida Vilaça; Sukanlaya Tantiwisawaruji; Maria João Rocha; Eduardo Rocha (Animals)
Global warming raises surface water temperatures, impacting fish alongside pollutants, such as ubiquitous xenoestrogens. Combined stressor effects are poorly studied but likely to worsen impacts and hinder biota adaptation, warranting further research. Unadapted fish face heightened risks. The liver is a vital metabolic organ, sensitive to temperature and xenoestrogens, eventually adjusting hepatocyte size and number to ensure survival, growth, and reproduction. This study assessed, for the first time, the impact of exposure (45 days) to thermal stress (29 °C versus 26 °C) and ethinylestradiol (EE2, 5 ng/L) on male guppies, primarily on body and quantitative liver morphology. Higher temperature reduced body mass (14%) and standard length (3.6%) gain. EE2 exposure reduced body mass increase (14%), hepatosomatic index (20%), and the volumes of the liver (32%), hepatocytes (16%), and their nuclei (17%). The nucleus-to-cytoplasm ratio and total hepatocyte number remained stable. No histopathological lesions existed. Guppies appear to have adapted to stressors by reducing hepatocyte size and utilizing lipid reserves, yet they exhibited deficits in body growth and hepatosomatic index. Gonadal maturation was unaffected. Only under EE2 at 29 °C did hepatocytes show minimal lipid droplet content (less vacuolation). This indicated exhausted reserves, reinforcing how heat and toxicants interact to exacerbate impacts.